1985
DOI: 10.1002/nur.4770080403
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of perimenstrual symptoms across two cycles

Abstract: The prevalence of perimenstrual symptoms usually is based on reports for one menstrual cycle; the consistency of symptoms across cycles is ignored. The purpose of this investigation was to determine perimenstrual symptoms reported concordantly for two menstrual cycles in a group of 63 presumably healthy women reporting symptoms in health diaries over 2 months. There were only nine symptoms for each of the menstrual and premenstrual phases reported by the same woman across both cycles. Furthermore, concordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Alternatively, long diary completion periods (greater than 6 months) may lower participation and completion rates (Gold, Weiss, Tager, Segal, & Speizer, 1989). For menstrual cycle research, a diary needs to be kept for at least two cycles because of the usual lack of symptom concordance between cycles (Shaver & Woods, 1985). Another alternative is the random selection of diary days within data collection periods.…”
Section: Types Of Health Diariesmentioning
confidence: 99%
“…Alternatively, long diary completion periods (greater than 6 months) may lower participation and completion rates (Gold, Weiss, Tager, Segal, & Speizer, 1989). For menstrual cycle research, a diary needs to be kept for at least two cycles because of the usual lack of symptom concordance between cycles (Shaver & Woods, 1985). Another alternative is the random selection of diary days within data collection periods.…”
Section: Types Of Health Diariesmentioning
confidence: 99%
“…Variability may also Premenstrual symptoms and ovarian hormones 69 occur within individuals from one cycle to the next (e.g. Schnurr, 1989;Green, 1982;Hart et al, 1987;Shaver and Woods, 1985;Walker, 1991). As Gise et al (1990) point out, events in people's lives (crises, holidays, physical illness etc.)…”
Section: The Nature Of Pmsmentioning
confidence: 97%
“…Asking women to retrospectively rate symptom severity for the postmenstrual and premenstrual phases of the past three menstrual cycles does not accurately reflect the symptom severity found on a day to day basis. Other investigators have found this same effect where individuals will magnify their retrospective symptom severity response or minimize their prospective ratings of symptom severity (Abplanalp, 1988;Shaver & Woods, 1986;Woods et al, 1987).…”
Section: Pms Typologies: Variations In Pna Symptom Severity Patternsmentioning
confidence: 97%